2021
DOI: 10.1515/eujal-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning beyond English in the Netherlands: A fragile future?

Abstract: The Netherlands have had a long tradition of modern foreign language (MFL) education: French, German and English have been standard subjects at secondary school since the 19th century. After the introduction of the Mammoetwet in 1968, several major educational reforms have shaped the current practice of Dutch MFL teaching. On the one hand, a greater diversity of languages is on offer in secondary schools (e. g., Arabic, Spanish), and following the implementation of the CEFR (Council of Europe 2001) MFL teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…1 For more information about the Dutch education system, see: https://www.nuffic.nl/en/subjects/education-in-the-netherlands/#secondary-education. See also Michel, Vidon, de Graaff & Lowie (2021). 2 In debate, a case is 'a cohesive set of [written] arguments [prepared beforehand] that justify the side of the topic that they have been assigned' (Snider & Schnurer, 2006, p. 26).…”
Section: Notesmentioning
confidence: 99%
“…1 For more information about the Dutch education system, see: https://www.nuffic.nl/en/subjects/education-in-the-netherlands/#secondary-education. See also Michel, Vidon, de Graaff & Lowie (2021). 2 In debate, a case is 'a cohesive set of [written] arguments [prepared beforehand] that justify the side of the topic that they have been assigned' (Snider & Schnurer, 2006, p. 26).…”
Section: Notesmentioning
confidence: 99%
“…For the most part, however, the greatest concentration of plurilingualism is in central Europe, and for bilingualism, we have the Nordic countries and the Baltic states, with monolingualism more prevalent among the former Warsaw Pact countries and in the south. As reported by Michel et al (2021: 171), for the Netherlands, ‘German and French show a steady decline from almost 60% and 30% in 1980 to 32% and 16% for German and French, respectively’. This is a common trend across mainland Europe, where the learning of both French and German have suffered because of the increasing interest in investing in the English medium as well as in Spanish.…”
Section: Western Europementioning
confidence: 75%
“…It seems that a predominantly implicit, DUB FL teaching program might be as effective as a predominantly explicit, SB approach in terms of achieving morphological accuracy and even more effective in achieving complexity and fluency. Apparently, students do not need a great deal of explicit instruction to become accurate in writing; therefore, it might be much more useful to spend time in class on oral skills, which are seriously neglected in most FL French classes in the Netherlands (Michel et al, 2021). As another study on the same students has shown (submitted), the DUB students outperform the SB students significantly with a very large effect size (d = 2.05) on speaking skills.…”
Section: Resultsmentioning
confidence: 99%